Efektivitas Kapur Tohor Terhadap Peningkatan Ph Dan Penurunan Kadar Logam Fe Dan Mn Di Settling Pond 11 PT. Alam Jaya Pratama Site Bara Kumala Sakti Kecamatan Loa Kulu, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Jovanda Ego Prisitama; Henny Magdalena; Shalaho Dina Devy (Retii, 2023)
The settling pond is the final location where water comes from the Pit, Sump, Disposal and run-off water around the mining location at PT. Alam Jaya Pratama site Bara Kumala Sakti. Water quality in settling pond that does not meet the Mining Activity Waste Water Quality Standards can be managed using chemicals, one of which is Calcium Oxide (CaO). The need for Calcium Oxide can be determined after knowing the most effective dose in the settling pond. Calcium Oxide functions to neutralize pH and reduce metal levels (Fe and Mn) in settling ponds. Based on facts in the field, the poor water quality for the surrounding environment is due to the management period being too long and the efficiency of using Calcium Oxide incorrectly. So that the quality of the water released can meet the standards, regular monitoring and testing of the water quality in the settling pond is required with the final aim of the water output being in accordance with the standards and the amount of Calcium Oxide needed in Settling Pond 11 can also be known. From the results of initial measurements on water samples at Inlet Settling Pond 11 was obtained an average pH of 3,25; levels of Fe 1,61 mg/L; levels of Mn 2,81 mg/L are below standard. By testing using the titration method, the average optimum dose for increasing pH and reducing metal levels was 1 mg/L. After each sample went through a titration test, the average was obtained, namely: pH 7,32; levels of Fe 0,46 mg/L; and levels of Mn 1,63 mg/L. From this average dose, the need for Calcium Oxide is 223,32 kg/month. The comparison of Calcium Oxide usage per month between actual and calculated is 500 kg : 223,32 kg. The recommendation from this comparison is that these results can be taken into consideration to optimize the use of Calcium Oxide in Settling Pond 11.